Rekonstruksi Teologi Emansipatoris Berbasis Aktualisasi Diri: Kritik atas Kemandekan Spiritualitas dalam Membongkar Struktur Penindasan Masyarakat - Aura Difa Putri Al-Kayyis; Siti Amirah Faizah Choirun Nisa; Yaumil Lailani; Ali Hasan Siswanto (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The persistence of oppression in contemporary society presents a serious paradox amidst the advancement of modernity and growing awareness of social justice. Normatively, Islamic theology affirms the principle of anti-oppression (zulm) through the values ​​of justice ('adl) and social monotheism, but in practice, spirituality is often reduced to ritual symbols that lack the power to social transformation. The research gap lies in the lack of integration between liberation theology, humanistic-existential psychology, and operational models of social movements. This study aims to reconstruct the paradigm of emancipatory theology based on self-actualization as a conceptual foundation for building a society without oppression.The theoretical approach used is the integration of Islamic theology with humanistic-existential psychology, specifically Abraham Maslow's concept of self-actualization. The research method employed is qualitative-conceptual through literature review with critical analysis, hermeneutics, and interdisciplinary synthesis. The main argument of this study asserts that oppression is not merely a structural phenomenon but also an existential crisis that hinders human development toward self-actualization. Therefore, authentic social transformation requires the reconstruction of individual consciousness and the simultaneous transformation of social systems. This research's scientific contribution lies in the formulation of a "Humanistic-Emancipatory Theology" paradigm that integrates spiritual, psychological, and social practical dimensions as a new conceptual model in contemporary Islamic studies. This paradigm not only enriches the theoretical literature but also offers an applicable framework for building social movements oriented toward holistic human liberation.